Rational functions please help me with this.?

Attachment image

2 Answers

Relevance
  • 1 month ago
    Best answer

    3x^2 + 4x + 1

    = 3x^2 + 3x + (x+1)

    = 3x(x+1) + (x+1)

    = (x+1)(3x+1)

    ....

    x^2 + x

    = x(x+1)

    so

    f(x)

    = (x+1)(3x+1) / (x(x+1)

    = (3x + 1)/x

    will leave the rest to you.....

  • Robert
    Lv 7
    1 month ago

    3x^2 + 4x + 1 = (3x + 1)(x + 1)

    x^2 + x = x(x + 1)

    So the expression simplifies to (3x + 1) / x

    You can take it from here!

Still have questions? Get answers by asking now.